Health Status of Dually Eligible Beneficiaries in Managed Care Plans - Lied, Terry R. (CENTERS for MEDICARE & MEDICAID SERVICES, 2004)
We conducted a descriptive study examining the health status of dually eligible beneficiaries using a sample from the Medicare Health Outcomes Survey (HOS), a measure of health status administered to enrollees in Medicare managed care (MMC). Overall, we found that dually eligible beneficiaries were sicker, more depressed, and reporting more pain than Medicare-only beneficiaries. Our results suggest that quality improvement initiatives that center on pain and depression management in the dually eligible population present important opportunities for collaboration between Medicare and Medicaid.